Team Member Work Role Performance: The Organizational Benefits From Performance-Based Horizontal Pay Dispersion and Workplace Benign Envy - Zhang, Haiyan; Sun, Shuwei; Zhao, Lijing (Frontiers in Psychology, 2020)
In the context of current uncertain, complex, and interdependent work systems, team has become organizations’ substantial working unit, which in turn challenges the traditional view of employee performance and ultimately results in the emergence of “team member work role performance.” Employee team-oriented work role behaviors with proficiency, adaptivity, and proactivity, which are integrated by the new construct, are so crucial to team effectiveness that many organizations keenly expect to achieve “team member work role performance” through implementing a dispersed pay-for-performance plan within a team. This study seeks to address organizational practitioners’ main concern that whether pay dispersion among team members (i.e., horizontal pay dispersion, HPD) could actually help realize “team member work role performance” and further examines “why” and “when” an employee could respond to HPD within a team by engaging in team member work role behaviors from the perspective of performance-shaping-basis and workplace benign envy. Drawing on emotion-related theory, social comparison theory, legitimacy theory, expectation theory, and relative deprivation theory, it proposes that performance-based HPD could not only positively impact team member work role performance via workplace benign envy but also exert a direct-positive effect. Moreover, the activating effect of performance-based HPD on workplace benign envy and the mediating role are much stronger when team member’s pay position is higher. The multi-source data including objective information and subjective perception among 362 ordinary employees within 66 Chinese organizational teams primarily supported the moderated mediation model. Yet, the direct-positive effect was not established.